FLASH MOBS SEBAGAI STRATEGI KOMUNIKASI PELIBATAN KONSUMEN MELALUI MEDIA SOSIAL DI INDONESIA (Lembaga Penerbitan Universitas Esa Unggul, 2013)
AbstractThe new media has brought change. Although in certain contexts, the old media still plays an important role in strengthening the civil society. But the new media, undeniably, now has emerged as the dominant force in the formation of the new civil society. Now, a new generation of so-called gen.com is growing up with strong characters and identities to foster a new culture in the new society. This paper focuse on the discussion of social movement in flash mobs formation as an offline socio-commercial activity. That is a continuation of the interaction of mass communication in the community of new online media such as email, social networking sites, and a variety of short messages in mobile-gadget. Virtual and physical activities also become a new commercial flash mobs entertainment include what some brands did in many cities in Indonesia. New media has given birth to and nurture a new behavioral and which is continuously maintained and preserved as a part of people’s life. So that online activities are realized in offline activities such as social action is a new culture in Indonesian society and global community. The integration of corporate communication that brings solution to the consumers through both of online and offline activities have been growing the power of new media culture in contemporary society, especially in urban and suburban contexts. Some specific issues are being the themes of socio-branding that be able to attract public to join in flash mobs such as health, mass dance, souvenirs, and then people can be aired on television. Smart companies usually follow variety of issues such as healthy life, public interest and welfare, the quality of environment, politics and democracy, transparency and against corruption, and others that coupled with entertaining people in urban space. Keywords: flash mobs, enganged consumers, social media